Asymptomatic gastric anisakiasis detected in gastric cancer screening: A case report. (2022) - Harada, Fumiue; Yamamoto, Kana; Takeuchi, Akio; Uenishi, Hiroshi; Tachiya, Yosuke; Yamamoto, Chika; Tani, Yuta; Ohnishi, Mutsuko; Takita, Morihito; Tanimoto, Tetsuya; Kami, Masahiro; Shineha, Ryusaburo
Abstract: Anisakiasis is a parasitic disease caused by Anisakis simplex and has become an emerging zoonosis as preferences for eating raw or undercooked seafood have become more common. Few case reports of asymptomatic anisakiasis have been published to date. A 79-year-old asymptomatic man underwent esophagogastroduodenoscopy (EGD) for gastric cancer screening. The gastroenterologist diagnosed superficial gastritis without any malignant lesions but found an Anisakis larva while reviewing EGD images. The physician performed a second EGD and removed the larva. The patient reported that he ate the flatfish sashimi for dinner on the day before the first EGD. This case indicates the existence of asymptomatic gastric anisakiasis, indicating that anisakiasis incidence may have previously been underestimated. Highlights: Anisakiasis is an emerging zoonosis due to eating undercooked marine products. Gastric anisakiasis often causes severe epigastric pain and allergic reactions. Few case reports on gastric anisakiasis have identified an asymptomatic form. Our case indicates the potential for underdiagnosis of anisakiasis. Anchor bias overlooking anisakiasis may occur during gastric cancer screening.